Pengaruh Kualitas Pelayanan terhadap Minat Beli Konsumen pada Rumah Makan Serba Ayam Kebun Cengkeh di Kota Ambon - Winda, Winda; Pelamonia, Merryl; Sinay, Francisca Riconita (Jurnal Pendidikan Ekonomi, 2024)
The increasingly competitive culinary business in Ambon City requires business owners to enhance service quality to attract consumer purchase intentions. This study aims to analyze the effect of service quality on consumer purchase intention at Serba Ayam Restaurant, Kebun Cengkeh. The research employed a quantitative approach with a survey technique using questionnaires distributed to 55 respondents and multiple linear regression analysis to examine the relationship between service quality dimensions and purchase intention. The results indicate that service quality, which includes physical evidence, reliability, responsiveness, assurance, and empathy, significantly influences consumer purchase intention, with the greatest contribution coming from reliability and responsiveness. The findings confirm that improving service quality can effectively drive consumer buying interest. The implication of this study emphasizes the need for restaurant managers to continually improve service standards according to consumer needs and recommends regular staff training to provide the best service and enhance customer loyalty